In Silico, In Vitro and In Vivo Pharmacodynamic Characterization of Novel Analgesic Drug Candidate Somatostatin SST4 Receptor Agonists - Kántás, Boglárka; Szőke, Éva; Börzsei, Rita; Bánhegyi, Péter; Asghar, Junaid; Hudhud, Lina; Steib, Anita; Hunyady, Ágnes; Horváth, Ádám; Kecskés, Angéla; Borbély, Éva; Hetényi, Csaba; et al. (Frontiers in Pharmacology, 2021)
Background: Somatostatin released from the capsaicin-sensitive sensory nerves mediates analgesic and anti-inflammatory effects via its receptor subtype 4 (SST4) without influencing endocrine functions. Therefore, SST4 is considered to be a novel target for drug development in pain, especially chronic neuropathy which is a great unmet medical need. Purpose and Experimental Approach: Here, we examined the in silico binding, SST4-linked G protein activation and β-arrestin activation on stable SST4 expressing cells and the effects of our novel pyrrolo-pyrimidine molecules (20, 100, 500, 1000, 2000 µg·kg-1) on partial sciatic nerve ligation-induced traumatic mononeuropathic pain model in mice. Key Results: The novel compounds bind to the high affinity binding site of SST4 the receptor, activate the G protein. However, unlike the reference SST4 agonists NNC 26-9100 and J-2156, they do not induce β-arrestin activation responsible for receptor desensitization and internalisation upon chronic use. They exert 65–80 % maximal anti-hyperalgesic effects in the neuropathy model 1 hour after a single oral administration of 100–500 µg·kg-1 doses. Conclusion and Implications: The novel orally active compounds show potent and effective SST4 receptor agonism in vitro and in vivo. All four novel ligands proved to be full agonists based on G protein activation, but failed to recruit β-arrestin. Based on their potent antinociceptive effect in the neuropathic pain model following a single oral administration, they are promising candidates for drug development.